Money in the House : campaign funds and congressional party politics - Currinder, Marian. (Transforming American politics series (2002), 2009)
"This book provides a compelling look at how the drive to raise campaign money has come to dominate congressional party politics. Author Marian Currinder examines the rise of member-to-member and member-to-party giving as part of a broader process that encourages ambitious House members to compete for power by raising money for the party and its candidates. In order to give for the good of the whole, lawmakers must devote ever increasing amounts of time to fundraising. The fundraising expectations for members who wish to advance in the chamber are even higher. Currinder argues that the new "rule of money" is fundamentally altering the way House members pursue power and the way congressional parties define and reward loyalty."--BOOK JACKET.